Metaalbewerkersbond van Gent : Ve Jaarlijksch verslag der werkzaamheden van 1 december 1900 tot 30 november 1901. - Bytebier, J.; De Clerck, J. (Gent : Volksdrukkerij, 1902)
Bibliotheek E. Anseele
Nederlands
Brochure